Mini-BESTest cutoff points for classifying fallers and non-fallers female older adults - Batistela, Rosangela A.; Rinaldi, Natalia M.; Moraes, Renato (Brazilian Journal of Motor Behavior, 2023)
BACKGROUND: The Mini-Balance Evaluation Systems Test (Mini-BESTest) is an efficient screening tool healthcare professionals use to predict the risk of falls in older adults. However, the Mini-BESTest cutoff scores to classify fallers and non-fallers were established using men and women in the same sample. Considering the higher number and prevalence of falls in older women, it is important to know the Mini-BESTest accuracy and the cutoff score specifically for this population. AIM: We examined the capability and accuracy of the Mini-BESTest for identifying fallers and non-fallers female older adults without neurological impairments and established the cutoff scores according to different age groups. METHOD:Eighty-one female older adults were classified into fallers (n=40) and non-fallers (n=41) groups according to their retrospective history of falls in the last 12 months. Fallers and non-fallers were divided into three age groups according to the following ranges: 65-69 years, 70-74 years, and 75+ years. We used the receiver operating characteristic (ROC) curves to determine the relative performances of the Mini-BESTest score for classifying participants with and without a history of falls. RESULTS: The Mini-BESTest is a good and highly accurate tool for identifying female Brazilian fallers and non-fallers. The Mini-BESTest cutoff scores established to classify fallers and non-fallers female older adults in the different age groups were 26 points for 65-69 years and 24 points for 70-74 years and 75+ years. INTERPRETATION: The Mini-BESTest is an important tool that health professionals in clinical practice can use to estimate the risk of falls for older Brazilian women.